An industrial quality control study on Super Industrial Corporation - Bangalan, Darwin P. (College of Engineering, 2003)
Super Industrial Corporation is a medium-sized company producing black and galvanized steel pipes, couplings, light gage structurals, schoolhouses, armchairs, and low-cost houses. Among these products, black and galvanized steel pipes contribute approximately 27 percent of the company's total annual sales. This product line was chosen for this reason, since improvements in process efficiency may translate to higher profile for the company. Furthermore, during the period under study, only this product line was in production. Data on results of production such as measurements of material properties, results of tests done on products, and number of accepted and rejected pipes for the months of January and February 2002 were obtained for the study. The Pareto chart was used to determine the most critical areas in the production. Because of its high rejection/rework percentage, the unacceptability of the pipe appearance was identified as the most vital problem. Another Pareto was constructed to identify the pipe characteristics that exhibits the most variation or deviation from the target. The Pareto showed that among the variable characteristics of the product, variation in pipe length and variation of zinc coating thickness contribute 87.3 percent of the off-target pipes. Three Cause and Effect diagrams were constructed to identify the causes of each problem. The factors that affect acceptability of the pipe in visual inspection are the immersion time of the pipes in the different baths, the time taken in draining the pipes of excess bath liquid, the temperature and dirt content of the baths, and the movement of the winch craned used to guide the pipes into different baths. Pipe length is affected by the precision of the cut-off device, the state of the measuring device, and the subjective differences in manual measurement. Coating thickness is affected by the viscosity of the zinc solution, the speed of immersion, the drainage angle, and the length of immersion time in the galvanizing bath. Three Shewhart Control Charts were constructed to determine if the process was in control or out of control. For the first problem, the p-chart was constructed, and for the 2nd and 3rd problem, the X-bar and R Charts were used. All processes were out of control. The out-of-control points with assignable causes were eliminated and new control limits were computed for subsequent data. Process capability analysis showed the marginal capability of the pipe cutting process, and the high capability of the galvanizing process. This indicates that if the processes were in control, then a fallout of 64 pipes per million and 21 pipes per million can be expected from the pipe cutting and galvanizing process, respectively. The current acceptance sampling plan was also analyzed. Because of the high rejection/rework rate in pipe appearance, the group suggests that the company retain its 100 percent visual inspection. For the inspection of pipe length and zinc coating thickness, the group suggests that the company retain its sampling plan for purposes of performance monitoring. Amendments in the sampling plan such as increased frequency of inspection or increase in sample size have no additional benefits in terms of higher probability of acceptance. To improve the galvanizing process in terms of pipe appearance, the group suggests that the company install additional inspection points after the pre-treatment baths. This is to prevent incurring additional costs by galvanizing pipes that will eventually be rejected because of failure in the pre-treatment process. The dipping process may also be modified by moving the pipes up and down within the bath, to ensure even coating on all areas of the pipes during dipping. New inspection forms may also be introduced to facilitate easier recording of additional data such as occurrences of each type of nonconformity. In the rotary cut-off area, the group suggests the replacement of the spring coil that activates the automatic cut-off. This will ensure faster response in the machine, thus making more precise and consistent cuts. For the reduction of variation in coating thickness, the group suggests that the company purchase a timer to monitor immersion times instead of relying on the operator to estimate it during dipping. The angle of drainage may also be standardized by marking the proper positions of the pipe ends during drainage on the glass frame separating the bath and the operator. The group also suggests that the company obtain additional thickness measurements. This would give the company more information about the output of the process, and provide more opportunities for process improvement. Lastly, the group suggests that the company implement SPC to monitor the process. This would require additional training, and would require the expertise to a professional. Benefits include increased efficiency and uniformity of output. This would earn the company immeasurable benefits in terms of goodwill and customer satisfaction, which may lead to increases in profits. Performance monitoring may also improve employee satisfaction as workers become more involved and aware in producing quality products.